The Role of Leadership in Shaping Strategic Management Decisions of MSME Owners in Indonesia - Aviyanti, Cut; Widyastuti, Tri (Dinasti International Journal of Management Science, 2024)
This study investigates the role of leadership in shaping the strategic management decisions of Micro, Small, and Medium Enterprises (MSMEs) owners in Indonesia. Utilizing a mixed-methods approach, we surveyed 250 MSME owners and managers across various sectors and conducted in-depth interviews to gain qualitative insights. Our findings reveal that entrepreneurial and transformational leadership styles are the most prevalent and influential, significantly driving strategic planning, innovation management, and competitive positioning. Transactional leadership, while important, plays a comparatively lesser role. Qualitative insights highlight the impact of personal networks, cultural values, and adaptive leadership in navigating regulatory challenges and leveraging government support. Additionally, digital transformation emerges as a critical factor for operational efficiency and market reach. These results suggest that leadership development programs should focus on enhancing entrepreneurial and transformational skills, and government policies should be tailored to the specific needs of MSMEs, with an emphasis on reducing bureaucratic barriers and improving digital literacy. This study provides valuable implications for policymakers and practitioners aiming to strengthen the strategic management capabilities of MSMEs in Indonesia.